2022
DOI: 10.2478/raon-2022-0040
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of haemophilia early arthropathy detection with ultrasound (HEAD-US) in children: a comparative magnetic resonance imaging (MRI) study

Abstract: Background Ultrasound (US) has been proven to be reliable in the assessment of early haemophilic arthropathy in the adult haemophilic population, however few studies so far focused on the reliability of US specifically in the paediatric haemophilic population. We were interested if the changing appearance of the growing bone hinders the ultrasonographic evaluation of the pathologic processes caused by haemophilic arthropathy. The aim of the study was to assess the reliability of US for evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, without ultrasound (US), the capability to discover subclinical synovitis is greatly diminished, principally in the elbows [10]. Plut et al [11] have demonstrated that US utilizing the HEAD-US (Hemophilia Early Arthropathy Detection with Ultrasound) method is a dependable tool for identification and assessment of hemophilic arthropathy in children in comparison to MRI. Regarding hemophilic pseudotumors, computed tomography (CT) has demonstrated to make the differential diagnosis reliable and to produce helpful knowledge on the magnitude of the lesion and the implication of the skeleton and adjacent organs [12,13].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…However, without ultrasound (US), the capability to discover subclinical synovitis is greatly diminished, principally in the elbows [10]. Plut et al [11] have demonstrated that US utilizing the HEAD-US (Hemophilia Early Arthropathy Detection with Ultrasound) method is a dependable tool for identification and assessment of hemophilic arthropathy in children in comparison to MRI. Regarding hemophilic pseudotumors, computed tomography (CT) has demonstrated to make the differential diagnosis reliable and to produce helpful knowledge on the magnitude of the lesion and the implication of the skeleton and adjacent organs [12,13].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Hemophilia Early Arthropathy Detection with Ultrasound (HEAD‐US) has been found to have good reliability with Magnetic resonance images to detect early joint damage 7–9 . Recently, using HEAD‐US, it has been reported that PwMH of over 20‐year‐old 90% showed arthropathy in the lower limb 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Hemophilia Early Arthropathy Detection with Ultrasound (HEAD-US) has been found to have good reliability with Magnetic resonance images to detect early joint damage. [7][8][9] Recently, using HEAD-US, it has been reported that PwMH of over 20-year-old 90% showed arthropathy in the lower limb. 5 Ageing has been determined as an important factor related to the advance of joint impairment independent of the severity of haemophilia.…”
Section: Introductionmentioning
confidence: 99%